2017
DOI: 10.2139/ssrn.3043233
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing the Energy Efficiency Gap: The Impact of Educational Programs, Online Support Tools and Energy-Related Investment Literacy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(58 reference statements)
2
8
0
Order By: Relevance
“…As discussed in Blasch et al (2017b), the higher marginal effect in the refrigerator experiment is likely due to the fact that in this experiment, the most cost-efficient appliance could only be identified when comparing lifetime usage costs of both appliances, which requires some calculation. Similarly, the marginal effects in Blasch et al (2017c) for the two decision aids, and for the choice of lifetime cost calculation strategy, are found to be very similar with the results reported in Table 9. 21 To summarize, the main model estimation results are found to be comparable to the results reported in Blasch et al (2017b) and Blasch et al (2017c) that uses separate variables for energy literacy (numeric score from 0 to 11) and investment literacy (dichotomous variable) -this provides support to the clustering approach as a sophisticated alternative to less refined aggregation strategies and serves as a robustness check towards the crucial role played by energy-related financial literacy in the domain of appliance choice.…”
Section: Robustness Check Of Previous Results Using the Clustering Apsupporting
confidence: 74%
See 4 more Smart Citations
“…As discussed in Blasch et al (2017b), the higher marginal effect in the refrigerator experiment is likely due to the fact that in this experiment, the most cost-efficient appliance could only be identified when comparing lifetime usage costs of both appliances, which requires some calculation. Similarly, the marginal effects in Blasch et al (2017c) for the two decision aids, and for the choice of lifetime cost calculation strategy, are found to be very similar with the results reported in Table 9. 21 To summarize, the main model estimation results are found to be comparable to the results reported in Blasch et al (2017b) and Blasch et al (2017c) that uses separate variables for energy literacy (numeric score from 0 to 11) and investment literacy (dichotomous variable) -this provides support to the clustering approach as a sophisticated alternative to less refined aggregation strategies and serves as a robustness check towards the crucial role played by energy-related financial literacy in the domain of appliance choice.…”
Section: Robustness Check Of Previous Results Using the Clustering Apsupporting
confidence: 74%
“…Table 8 finds a positive role of both MID-literacy and HIGH-literacy groups on the probability to opt for a lifetime cost calculation strategy and in turn to identify the appliance with the lowest lifetime cost. The two decision aids (TRSLIDE and TRCALC) are found to have a positive impact on the probability that an appliance with the lowest lifetime cost is chosen and, similar to the results in Blasch et al (2017c), the calculator tool is found to be more effective than the information slides. Table 9 reports the marginal effects of our variables of interest similar to the ones reported in the two studies.…”
Section: Robustness Check Of Previous Results Using the Clustering Apsupporting
confidence: 56%
See 3 more Smart Citations